Local Wisdom Of Kampung Naga In Achieving Sustainable Tourism - Dwiatmini, Sriati; Aras, Taufik Setyadi (Universitas Andalas, 2024)
Kampung Naga is located in Tasikmalaya Regency, West Java, where the people still maintain and carry out the customs inherited from their ancestors in their daily lives. It is considered unique, so many tourists visit. The arrival of tourists from various cultural backgrounds has been going on for more than four decades, to some extent influencing the daily lives of the people of Kampung Naga. The aim of this research is to describe local wisdom related to tourism in the Kampung Naga community. The formulation of the problem is how do the people of Kampung Naga construct local tourism wisdom, and what form does it take? To answer this, a qualitative description method was used, through the stages of observation, interviews and interpretation. The results of the analysis show that the people of Kampung Naga construct local tourism wisdom which is the result of interactions between the culture of the community and the culture of tourists, as well as tourism development carried out in their village. Local tourism wisdom is based on harmonizing relations between tourists and local residents based on kinship and tourism management based on mutual cooperation.